Preparation, characterization and optimization of superhydrophobic PVDF-PVC composite membrane based on concentration change of casting solution. (30th December 2020) - Zhang, Dashuai; Lin, Xiaoxue; Zhang, Yan; Zhang, Xiaopeng; Li, Chen; Lin, Yang; Sun, Tianyi; Zhu, Linhua; Lin, Qiang; Shi, Zaifeng
Abstract: The PVDF/PVC superhydrophobic composite membrane was prepared by non-solvent induced phase separation method. When the concentration of PVDF/PVC(= 85/15) is 4%, DMF can be used as a solvent to prepare PVDF/PVC superhydrophobic composite membrane by using the simple and applicable NIPS method. Through static contact angle and rolling angle, it was found that the maximum contact angle of PVDF/PVC composite membrane with low concentration can reach 152°, rolling angle is 3 degrees, and the surface potential energy is also relatively low about 8°. It was found by DSC that the crystallinity of PVDF/PVC composite membrane with low concentration was higher, SEM shows that the surface of 4% PVDF/PVC composite membrane has nano scale protrusion, and AMF finds that the surface of 4% PVDF/PVC composite membrane was high Surface roughness. When the surface roughness was high, the surface hydrophobicity is improved, the wetting problem was alleviated, the self-cleaning ability of the membrane is improved, and the membrane pollution is reduced. It was found that the 4% PVDF/PVC composite membrane prepared by low concentration method has a long-lasting self-cleaning performance and can be used as an organic coating in the field of self-cleaning.